Od Wielicka do Woli Suchożebrskiej albo historia jednego pytania - Makowiecka, Maria Hanna (2022)
The creation of this book relates to the story of a certain question that not only started a whole series of subsequent ones, but eventually led to interviews with numerous witnesses of dramatic events and to the telling of their fates. All events revolve around the landed Makowiecki family, whose fate we begin to follow from the nineteenth century. Its representatives and, at the same time, our main characters are Stanislaw and Sophia Makowiecki. The panorama of their history is sketched from their idyllic life in a manor house in Wielick, Volhynia, to the purchase of a new manor house in Wola Suchożebrska near Siedlce just before the outbreak of World War II. Wandering with them through pre-war Volhynia, then through the harsh years of occupation in wartime Podlasie, we reach the events woven into the history of post-war Poland and Warsaw, i.e. the communist years of the Polish People's Republic. And we part with their descendants already in free, modern Poland.     Most attention was paid to the Makowiecki family's stay and activities in Wola Suchożebrska. For with this manor and this stage of their lives, fate has tied various war refugees. Among them are a well-known doctor and at the same time a great hero, who managed to get news about the secret program of building V-2 rockets. There are soldiers from the Home Army in hiding and Russians from a prisoner of war camp. There are children from the RGO in safekeeping in a rural environment, including Jewish children, there are Jesuit priests, there is a former commissioner and governor of Siedlce and former Auschwitz and Ravensbruck prisoners.Interviews conducted with event participants and witness testimonies, gathered into unique narratives, enrich and bring closer to the reader not only the events of Great History but also the realities of everyday life at that time. Previously unpublished numerous photographs perfectly illustrate the captured past. The polyphony of these testimonies is complemented by previously unknown archival and private, often intimate, materials, letters.Thanks to these relationships and archives, the ordinary family history ceases to be a monograph of just one family. By bringing closer locally important matters and historical facts, it becomes a universal contribution that enlivens the national past.